OpenUP Measuring Research Impact: Concepts, Methods, Limitations and Solutions - Walker, Mappet; Oeben, Stephanie; Walker, Richard (Septentrio Conference Series, 2018)
Watch the VIDEO. The immediate Return on Investment (ROI) for basic scientific research is scientific impact – improvements in knowledge of our physical, biological and social world. The Return on Investment (ROI) for applied research and the long-term Return on Investment for basic research is societal impact (i.e. impact on health, environment, the economy, etc.). However, many of these impacts are hard to measure and may only be apparent decades after the original investment. This creates demand from funders and policy makers for metrics that predict impacts before they can be measured. Here we define a preliminary conceptual framework describing the chain of events leading from the outputs of basic research (publications, data, software, cell lines, equipment, methodologies, theories etc.) to the outputs of applied research (products, treatments, technology components etc.) to societal, financial, health and environmental impact. We go on to discuss how these impacts are currently measured in the short term (days and weeks), the medium term (years) and the long term (decades), and to identify the main providers of impact metrics. We highlight the different ways in which research metrics are used by different categories of user (researchers, institutions, national and European policymakers). Finally, we discuss the limitations of current metrics and possible solutions.